Supervision of the Election Supervisory Agency (Bawaslu) in Maintaining the Neutrality of Civil Servants (ASN) during the 2024 Simultaneous Regional Head Election in Medan City - Sabrina, Diva (SAJJANA: Public Administration Review, 2026)
The neutrality of the State Civil Apparatus (ASN) is a fundamental principle in regional head elections to ensure a fair, democratic, and impartial electoral process. However, violations of ASN neutrality were still found during the 2024 Simultaneous Regional Elections, including in Medan City. This study aims to analyze the supervision conducted by the General Election Supervisory Agency (Bawaslu) of Medan City in maintaining ASN neutrality during the 2024 Simultaneous Regional Elections. This research employed a descriptive qualitative approach. Data were collected through interviews, observations, and documentation and analyzed using Robbins and Coulter’s (2016) supervision theory. The findings show that Bawaslu of Medan City carried out its supervisory duties by establishing supervision standards, monitoring ASN activities, implementing preventive measures, handling reports and findings, and submitting recommendations to the relevant authorities. However, supervision remains constrained by limited human resources, the broad scope of supervision, uneven public outreach, and the limited understanding of neutrality regulations among some ASN.